Review: Analisis Peran Tenaga Kesehatan dalam Kesiapsiagaan Menghadapi Bencana Banjir di Kabupaten Malang Jawa Timur - Lilis Sulistiya Nengrum (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
A disaster is in an area that results in ecological damage, loss of human life, and deteriorating health and meaningful health services that require extraordinary assistance from outside parties. There is a role for health services in the community with disaster management in a state of disaster. This study aimed to analyze the role of health workers in flood disaster preparedness in Malang regency, east java. The research design used is a descriptive method with the cross-sectional approach, with a sample of 107 respondents. The research results show that health workers' role in flood disaster preparedness is 71 people (66,4%), and 21 people (19,6%) have a good role. The conclusion of this study shows that the role of the majority of health workers is sufficient. It is hoped that this research needs to be increased in health workers' role in disaster management and disaster services.